Urban forest, trees, and greenspace : a political ecology perspective - Sandberg, L. Anders 1953-; Bardekjian, Adrina; Butt, Sadia (London ; New York : Routledge, Taylor & Francis Group, Earthscan from Routledge, 2015)
Includes bibliographical references and index